2022
DOI: 10.3390/bioengineering9100584
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Mortality in Hospitalized Patients with COVID-19 during the Omicron Wave in Brazil

Abstract: Considering the imminence of new SARS-CoV-2 variants and COVID-19 vaccine availability, it is essential to understand the impact of the disease on the most vulnerable groups and those at risk of death from the disease. To this end, the odds ratio (OR) for mortality and hospitalization was calculated for different groups of patients by applying an adjusted logistic regression model based on the following variables of interest: gender, booster vaccination, age group, and comorbidity occurrence. A massive number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…Furthermore, the older cohort of 60-79 years has a higher burden of NCDs compared to their younger counterparts in Nepal. Global data showed that the highest death rate was noted in those with cardiovascular diseases, followed by diabetes, chronic respiratory diseases, hypertension, and cancer [30][31][32]. Our study showed that 4 in 10 deceased had hypertension and almost 1 in 3 had type 2 diabetes, compared to the national prevalence of hypertension of 32% (95% CI: 23%-40%) [33] and type 2 diabetes of 8.5% (95% CI: 6.9%-10.4%) [34] among the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the older cohort of 60-79 years has a higher burden of NCDs compared to their younger counterparts in Nepal. Global data showed that the highest death rate was noted in those with cardiovascular diseases, followed by diabetes, chronic respiratory diseases, hypertension, and cancer [30][31][32]. Our study showed that 4 in 10 deceased had hypertension and almost 1 in 3 had type 2 diabetes, compared to the national prevalence of hypertension of 32% (95% CI: 23%-40%) [33] and type 2 diabetes of 8.5% (95% CI: 6.9%-10.4%) [34] among the adult population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to antibody staining the cells were stained with the fixable viability dye, Zombie (Biolegend, USA) in PBS. The cells were stained with antibodies against CD3, CD4, CD8, IFN-γ, TNF-α, IL-2 and IL1-β (Biolegend, USA), Approximately 1×10 5 cells were acquired using a LSRII Flow Cytometer (Becton Dickinson, USA) and the data analysed using FloJo software (version 10.1; Treestar, USA). Dead cells were excluded from the scatter plots prior to analysis, and negative gates were set using fluorescence minus one (FMO) controls.…”
Section: Online Materials and Methodsmentioning
confidence: 99%
“…Case fatality risk (CFR) in hospitalised patients, and particularly in mechanically ventilated patients, during the Beta and Delta waves was particularly high (~50%-70%; 1 ). Even with the Omicron-related variants, CFR remains significant in the elderly and immunocompromised persons, and in several countries including the UK, Italy, France, Brazil, and China where there is an unfolding epidemic of severe COVID-19 disease [2][3][4][5][6][7][8][9][10] .Better therapeutic interventions are needed. However, despite considerable research, the pathogenesis of severe COVID-19, relative to viral kinetics, remains incompletely understood.…”
mentioning
confidence: 99%
“…In summary, the clinical characteristics of COVID‐19 caused by Omicron might be different from those of the original strain. Currently, studies have primarily focused on the clinical characteristics and risk factors for severe illness caused by Omicron subvariants BA.1 and BA.2 15–17 . And no studies have comprehensively investigated the clinical characteristics and factors for critical illness caused by Omicron subvariant BF.7.…”
Section: Introductionmentioning
confidence: 99%